The Protest of Tofu-Tempe Producers : A Content Analysis of Print Media - hendarto, kresno agus; Dharmmesta, Basu Swastha; Purwanto, B M; Moeliono, Moira M.M (Jurnal Manajemen Teknologi, 2013)
Tofu-tempe has been popular among the Indonesia people. Nearly all people have ever consumed them. However with the long draught in the last half century in United States of America, the price of soybean, the raw material of tofu-tempe, has increased significantly. Consequently, the producers of tofu-tempe in Jakarta protested. They stopped the production for 3 days from 25 to 27 July 2012. The relation between media and protest is transactional. On the one hand, the protesting group uses media to disseminate their activities. On the other hand, media needs news to report. The objective of this study is to describe the protest of tofu-tempe producers. Therefore, this study attempts to answer some questions: (i) what is the root caused and what have triggered the protest? (ii) what is the target and what is the objective of the protest? (iii) who is benefited by the protest? and (iv) why the producers participated in the protest? Data on the protest by tofu-tempe producers were collected from media and analyzed by content analysis. The results showed that the roots caused of the protest were: (a) inability of the government to provide self-sufficiency of soybean; and (b) inability of the government to control the supply of soybean at national level and the trigger of the protest was significant increase of soybean price. They have made the producers protested. The objective of the protest were: (a) taking over of soybean trade by the government; (b) elimination of import tariff for soybean; (c) socialization to the society that soybean price has increased so that the society can understand the increase of selling price; (d) subsidy to soybean price to the producers of tofu-tempe; and (e) showing to the government the suffering of producers of tofu-tempe after the soybean price increase. The targets of the protest were the government; and the people most benefited by the protest were soybean importers. Â Keywords: protest, media, agenda setting, social dilemma theory, qualitative content analysis.